Exploring Indonesia's CO2 Emissions: The Impact of Agriculture, Economic Growth, Capital and Labor - Maulidar, Putri; Fitriyani, Fitriyani; Sasmita, Novi Reandy; Hardi, Irsan; Idroes, Ghalieb Mutig (Graha Primera Saintifika, 2024)
This study examines the dynamic impact of agriculture, economic growth, capital, and labor on carbon dioxide (CO2) emissions in Indonesia from 1990-2022. Employing the Autoregressive Distributed Lag (ARDL) method, the findings indicate that agriculture plays a substantial role in decreasing CO2 emissions in the short and long run. Additionally, a consistent positive correlation exists between economic growth and CO2 emissions, underscoring the difficulty in decoupling economic progress from its environmental repercussions. Capital formation, on the other hand, exerts a noteworthy negative influence on CO2 emissions, particularly in the long run, implying that increased investment in capital formation, potentially in environmentally friendly technologies, could contribute to a gradual reduction in emissions. However, the expanding labor is identified as a significant driver of CO2 emissions, particularly in the long run. Highlighting the challenges associated with mitigating the environmental impact of workforce growth. Furthermore, the Granger causality results indicate unidirectional causality from CO2 emissions and labor to agriculture, from agriculture to economic growth and capital formation, and from economic growth to capital formation. Therefore, promoting sustainable agriculture, aligning economic growth with green technologies, incentivizing eco-friendly investment, integrating comprehensive planning, and maintaining flexible policies are crucial for Indonesia's effective environmental and economic management.